Perkawinan Semarga Masyarakat Batak Mandailing Migran di Yogyakarta - Muslim Pohan (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2018)
Surname marriage is a marriage that is prohibited in the Batak custom, as a family is considered a blood line from the father. There are 3 (three) customary marriage systems, exogamy, endogamy and eleutrogamy. Marga marriages carried out by Batak Mandailing migrant communities in Yogyakarta experienced a shift in meaning from traditional Batak culture, from an exogamy marriage system to an eleutherogamy marriage system that did not recognize any restrictions as in the exogamy or endogamy marriage system. The factors that influence the same-sex marriage in the Batak Mandailing community of migrants are caused by factors of love, religious factors, economic factors, educational factors and cultural factors. The same-sex marriage in the Batak Mandailing migrant community was carried out because the Batak Mandailing migrant community did not believe in taboo.